2020
DOI: 10.1590/1806-9061-2019-1101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of E. Coli Infection on the Expressions of TGF-β/Smads Signaling Pathway in Broiler Intestine

Abstract: This experiment aimed to investigate whether Escherichia coli (E. coli) infection could affect the TGF-β/smads signaling pathway in the jejunal tissue of chickens. One-day-old Cobb 500 broilers were randomly divided into 2 groups and treated with intraperitoneal E. coli or broth injection. Clinical signs of the birds were assessed every day. Spleen and bursa of Fabricius of the birds, post-infection (pi), were collected to evaluate immune organ index. Jejunal tissues were collected to ascertain the expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In our study, we found an association between TGF-β signaling pathway and PdAc 4 -induced spleen toxicity, consistent with previous observations that the expression of TGF-β2 and TGF-β4 proteins and downstream SMAD2 and SMAD7 proteins in the spleen is signi cantly increased after E. tenella infection, indicating the involvement of the TGF-β signaling pathway in the spleen immune response to infection [36]. The TGF-β signaling pathway has also been reported to be involved in increased spleen index induced by E. coli infection in broiler chickens and in the expression of genes associated with defective DNA repair and cell proliferation in the spleen of patients with primary myelo brosis [37,38]. Additionally, the TGF-β signaling pathway contributes to increased spleen index induced by Fuzhengxiaoyan decoction treatment [39].…”
Section: Signaling Pathways Related To Pdac 4 -Induced Spleen Toxicitymentioning
confidence: 99%
“…In our study, we found an association between TGF-β signaling pathway and PdAc 4 -induced spleen toxicity, consistent with previous observations that the expression of TGF-β2 and TGF-β4 proteins and downstream SMAD2 and SMAD7 proteins in the spleen is signi cantly increased after E. tenella infection, indicating the involvement of the TGF-β signaling pathway in the spleen immune response to infection [36]. The TGF-β signaling pathway has also been reported to be involved in increased spleen index induced by E. coli infection in broiler chickens and in the expression of genes associated with defective DNA repair and cell proliferation in the spleen of patients with primary myelo brosis [37,38]. Additionally, the TGF-β signaling pathway contributes to increased spleen index induced by Fuzhengxiaoyan decoction treatment [39].…”
Section: Signaling Pathways Related To Pdac 4 -Induced Spleen Toxicitymentioning
confidence: 99%